2022
DOI: 10.4193/rhin21.275
|View full text |Cite
|
Sign up to set email alerts
|

Measuring control of disease in Chronic Rhinosinusitis; assessing the correlation between SinoNasal Outcome Test-22 and Visual Analogue Scale item scores

Abstract: Background: In chronic rhinosinusitis (CRS), aim of treatment is control of disease. EPOS2020 suggests the use of visual analogue scale (VAS) measurements on several symptoms. We aim to determine if individual VAS items can be replaced by widely used SinoNasal Outcome Test-22 (SNOT-22) items when determining control of disease, to avoid using double measurements and to stimulate its use in clinical practice. Methods: Analyses were made on correlations between individual SNOT-22 scores and symptom-specific ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Assessment of biological response and current CRS control was respectively performed per EUFOREA2023 and EPOS2020 11,27 . As cutoff points for the assessed criteria, related SNOT‐22 item scores of >3 and ≤3 were used respectively for the in EPOS2020 suggested cutoff points VAS >5 and ≤5, which are virtually interchangeable 51 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of biological response and current CRS control was respectively performed per EUFOREA2023 and EPOS2020 11,27 . As cutoff points for the assessed criteria, related SNOT‐22 item scores of >3 and ≤3 were used respectively for the in EPOS2020 suggested cutoff points VAS >5 and ≤5, which are virtually interchangeable 51 …”
Section: Methodsmentioning
confidence: 99%
“…11,27 As cutoff points for the assessed criteria, related SNOT-22 item scores of >3 and ≤3 were used respectively for the in EPOS2020 suggested cutoff points VAS >5 and ≤5, which are virtually interchangeable. 51…”
Section: Standardized Follow-up and Data Collectionmentioning
confidence: 99%
“…It can be largely divided into four domains: rhinologic (nasal obstruction, runny nose, cough, sneezing, loss of smell, posterior nasal drip), sleep disorder (difficulty in falling asleep, frequent wake up, lack of deep sleep waking up tired) psychological dysfunction (lack of concentration, anxiety, irritable, embarrassed, sad), and ear/facial symptoms (earfullness, ear pain, dizziness, facial tenderness or pain) [ 21 ]. The total score and the score of each domain reflect the overall disease burden and HRQOL status in patients with CRSwNP [ 18 , 19 , 20 , 21 , 22 , 23 ]. In this study, the HRQOL status was determined preoperatively and at the last follow-up date postoperatively using SNOT-22.…”
Section: Methodsmentioning
confidence: 99%
“…The exact definition of CRS control -its criteria and how to measure those criteria -remains a topic of investigation (90,341,342) . Recent studies have shown that patients' and healthcare providers' views of CRS control largely align (343) and that patients' assessments of their own CRS control reflects their CRS disease burden (344) .…”
Section: Disease Controlmentioning
confidence: 99%